Long-range energy migration in photoexcited polymers - Yu, JW; Kim, JK; Cho, HN; Kim, DY; Kim, CY; Song, NW; Kim, D (AMER CHEMICAL SOC, 2000)
Excitation migration dynamics and the energy-transfer process in a donor-acceptor pair system on photoexcitation have been investigated by using static and time-resolved photoluminescence (PL) measurements. The PL spectrum of poly(N-vinylcarbazole) (PVK) was fully superposed on the electronic absorption spectrum of poly(9,9'-di-n-hexyl-2,7-fluorenylvinylene (PDHFV) to fulfill a requirement for an efficient Forster-type energy transfer. In the PL spectrum of a blended PVK film with 0.5 wt % PDHFV on photoexcitation at 340 nm, the PL emission of PDHFV, which exhibits little absorbance at the excitation wavelength, prevailed over the PL emission of PVK. The PL spectrum of a bilayered structure with a PVK layer thickness of 4 mu m and a PDHFV layer thickness of 80 nm, which was prepared by spin-casting PDHFV solution in trichloroethylene on a PVK film, also showed the PL emission of PDHFV on photoexcitation of the PVK layer at 340 nm without a trace of the PL emission of PVK. Excitation energy migration through a PVK bulk was observed up to a PVK thickness of 23 mu m. A time-correlated single-photon counting (TCSPC) study deduced an energy migration velocity of 3.5 x 10(6) cm/s and a dwell time between each hopping of 85 fs, respectively, in the PVK bulk of the bilayered structures with a PDHFV layer thickness of 10 or 80 nm.